INFLAMMATION IS INCREASED IN NON-CALCIFIED / MIXED LEFT MAIN CORONARY PLAQUES AND IS MODIFIABLE BY STATINS: A MULTI-CENTER PET-CT STUDY - Subramanian, Sharath; Marincheva-Savcheva, Gergana; Medina, Hector; Maurovich-Horvat, Pal; Abdelbaky, Amr; Vijayakumar, Jayanthi; Mogg, Robin; Shankar, Sudha; Rudd, James; Fayad, Zahi; Brady, Tom; Hoffmann, Udo; et al. (Journal of the American College of Cardiology, 2012)
LM inflammation was assessed with FDG-positron emission tomography (FDG-PET) at 0 and 12 wks, and LM FDG signal was recorded as a target to background ratio (TBR).